Intravascular papillary endothelial hyperplasia associated with hemangioma of the mandible: A rare case report. Issue 1 (January 2016) - Tanio, Shunsuke; Okamoto, Atsuhiro; Majbauddin, Abir; Sonoda, Masayuki; Kodani, Isamu; Doi, Rieko; Ryoke, Kazuo
Abstract: Intravascular papillary endothelial hyperplasia (IPEH) is unusual, benign lesion of vascular origin caused by exuberation of endothelial cell proliferation. It is rarely seen in the oral region. Previous studies on oral IPEH revealed that the lower lip is the most frequent site, followed by tongue, upper lip, buccal mucosa and mandibular vestibule. We report a case of IPEH associated with hemangioma of the mandible of a 75-year-old male. Embolization of the inferior alveolar artery was performed in this case and the lesion was removed under general anesthesia the day after embolization. Histopathologically, intravascular proliferation of papillary processes within hemangioma was found. Immunohistochemically, the endothelial cells were positive for CD34. In this case, IPEH was observed in preexisting varices, hemangiomas, pyogenic granulomas, or lymphangiomas, known as a secondary (mixed) form. Continuous and careful observation is needed, because recurrence of the mixed form has been mostly reported due to incomplete excision or regrowth of the underlying lesion.